Photonic nanoarchitectonics with stimuli-responsive 2D materials. Issue 3 (18th March 2019) - Ganter, Pirmin; Lotsch, Bettina V.
Abstract : The emerging field of photonic nanoarchitectonics based on stimuli responsive 2D materials is highlighted with a focus on applications in colorimetric sensing. Abstract : The ability to produce structural color from inherently colorless materials, similar to that in butterfly wings and beetle shells, has attracted considerable research interest over the last three decades. Despite their extraordinary properties and performances, the field of structural colors based on inherently functional 2D materials only took off recently. In this minireview, we highlight the diversity of 2D materials utilized for achieving structural coloration in different architectures. We summarize the large tunability of photonic architectures based on 2D materials and emphasize their extraordinary dynamic response induced by external stimuli. Subsequently, recent strategies to tailor their properties with molecular and structural approaches are discussed. Finally, we point out promising future directions in this emerging field.